DEVELOPING DIDACTIC GAMES TO IMPROVE THE MATHEMATICAL SKILLS OF YOUNG CHILDREN - Santum, Pornsiri; Sittipon, Wanitcha; Nakhasiri, Varaporn (International Online Journal of Education and Teaching, 2023)
The objective of this research aims to develop didactic games to improve the mathematical skills of young children. Twenty-two students of early childhood students, ages 5 to 6 years old, and enrolled in kindergarten class Rajamangala Demonstration Kindergarten School, Thailand. The experiment was 8 weeks-3 days a week, and 40 minutes each day. The research instruments included an experience activity plan, educational media, an early childhood mathematics skills observation form, and a satisfaction assessment form. Mean, standard deviation, and One-way ANOVA were used for data analysis. The results showed that the math skills of the young children were improved after the experiment by the .01 level of statistically significance and the satisfaction of the teachers and educational personnel were at a high level.